The significance of the emotional intelligence of a university teacher for students - Savely Evgenievich Cherkezov; Elena Vladimirovna Efimova; Tatyana Nikolaevna Nikolaevna Sharypova (Вестник Майкопского государственного технологического университета, 2023)
The transfer of education into the sphere of rendering services expands the status of a university teacher with the relevant competencies of a manager of educational interaction. The recognition of emotional intelligence as one of the main components of the professional success of a modern specialist actualizes the need to develop the skills of understanding and managing emotions in a university teacher.The research problem is the awareness of the need for the development of emotional intelligence in a university teacher. The purpose of the research is to determine the significance for students of the presence of basic skills of emotional intelligence in a teacher.The research methods are questioning, analysis, synthesis, generalization.The results of the study are as follows: a questionnaire has been developed on the basic communication skills of emotional intelligence; students' survey has been conducted to identify their attitude to a teacher's emotional competence; the following skills have been prioritized: to address them by name; to be friendly when communicating; to give emotional color to the material presented; do not interrupt students in the process of communication; to be able to feel his emotional state and, on the basis of this, to build communication with him.Key conclusions: students are aware of the need for a teacher to carry out professional activities based on emotional intelligence; they expect a positive manifestation of his emotional competence associated with interpersonal interaction; remote learning mode actualize the competent manifestation of the emotional intelligence of the teacher, performing a compensatory function in remote interaction.